2018
DOI: 10.1590/2175-3369.010.supl1.ao09
|View full text |Cite
|
Sign up to set email alerts
|

O programa de aceleração do crescimento no estado da Bahia e os desafios da universalização do saneamento básico

Abstract: Resumo A universalização do saneamento básico no Brasil é um desafio diante do deficit e das desigualdades de acesso. A partir do início dos anos 2000, houve uma mudança no cenário nacional, com a ampliação de recursos, a melhoria da capacidade institucional e a definição de marco legal. Porém, não houve uma avaliação das ações, principalmente do PAC Saneamento. O presente estudo analisa esse programa na Bahia em relação aos desafios da universalização. A metodologia envolveu pesquisa documental e análise de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
3
0
4
Order By: Relevance
“…Recent years have witnessed an increase in the coverage of sanitation services, but universal access to this type of service in Brazil is still a challenge, far from being reached. Various studies have reported this difficulty, emphasizing the difference in access between different regions of Brazil and between income and schooling levels, resulting in the production of a divided society, with different access to fundamental rights such as basic sanitation (Law n. 11,445) 28,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have witnessed an increase in the coverage of sanitation services, but universal access to this type of service in Brazil is still a challenge, far from being reached. Various studies have reported this difficulty, emphasizing the difference in access between different regions of Brazil and between income and schooling levels, resulting in the production of a divided society, with different access to fundamental rights such as basic sanitation (Law n. 11,445) 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…The program's design featured a set of legislative and administrative measures and investment policies, aimed at stimulating growth of the country's economy, earmarking resources for priority infrastructure areas (logistics, energy, transportation, housing, and sanitation, among others). However, for actions in sanitation, although the PAC led to the expansion of funding and favored the resumption of investments in the area, it was not sufficient to develop measures and actions to fully meet the guidelines of the Brazilian National Basic Sanitation Law 29 . Since the program aimed to contribute to the country's development, strengthening the national path to economic growth, the PAC adhere closely to an economic and technocratic logic, prioritizing most of the budget resources for sectors that favor capital gain, with sanitation works left in second place.…”
Section: Discussionmentioning
confidence: 99%
“…Hand hygiene, a preventive measure for COVID-19, 14 is still a privilege in Brazil, since in several regions of the country, many homes do not have access to water and basic sanitation. 45 Because universal access to water and basic sanitation has not yet been implemented, 11 this basic human right remains far from being achieved. 13 Absence of universal access directly impacts the population's health 12 and constitutes an avoidable iniquity.…”
Section: Final Remarksmentioning
confidence: 99%
“…Este teve como foco o estímulo ao crescimento da economia do país, por meio da destinação de recursos para áreas prioritárias de infraestrutura. Porém, apesar do grande investimento na área do saneamento básico, a concepção e a implementação do PAC apresentou uma série de contradições e fragilidades, especialmente para fazer frente aos desafios da universalização dos serviços no país (Cunha, Borja, 2018). Estudo sobre o impacto de ações assistenciais e mudanças socioeconômicas e sanitárias na mortalidade de crianças, após o estabelecimento das metas dos ODM, evidenciou grande influência das condições sanitárias na proposição de um modelo de regressão múltipla, sugerindo que este indicador contribui para o acesso e cuidado à saúde das crianças (Marinho et al, 2020).…”
Section: E Firmado O Pacto Pela Redução Daunclassified